2022
DOI: 10.1038/s41401-022-00895-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and pharmacokinetics of VV116, an oral nucleoside analog against SARS-CoV-2, in Chinese healthy subjects

Abstract: VV116 (JT001) is an oral drug candidate of nucleoside analog against SARS-CoV-2. The purpose of the three phase I studies was to evaluate the safety, tolerability, and pharmacokinetics of single and multiple ascending oral doses of VV116 in healthy subjects, as well as the effect of food on the pharmacokinetics and safety of VV116. Three studies were launched sequentially: Study 1 (single ascending-dose study, SAD), Study 2 (multiple ascending-dose study, MAD), and Study 3 (food-effect study, FE). A total of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 17 publications
0
48
0
1
Order By: Relevance
“…Molnupiravir and Paxlovid were indicated for un-hospitalized cases with high risks for severe illness within 5 days after symptom onset and proved to be effective [ 12 , 13 ]. VV116 is an oral drug with robust anti-SARS-CoV-2 efficacy in preclinical studies and satisfactory safety, tolerability, and pharmacokinetic properties in healthy Chinese subjects [ 5 , 6 ]. In this study, VV116 significantly accelerated the viral shedding by 2–3 days when applied at the early stage of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molnupiravir and Paxlovid were indicated for un-hospitalized cases with high risks for severe illness within 5 days after symptom onset and proved to be effective [ 12 , 13 ]. VV116 is an oral drug with robust anti-SARS-CoV-2 efficacy in preclinical studies and satisfactory safety, tolerability, and pharmacokinetic properties in healthy Chinese subjects [ 5 , 6 ]. In this study, VV116 significantly accelerated the viral shedding by 2–3 days when applied at the early stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…VV116 is a new effective oral nucleoside drug candidate against SARS-CoV-2, which could inhibit SARS-CoV-2 replication, lower viral RNA levels and infectious virus titres in vivo and in vitro , along with satisfying tolerability safety and pharmacokinetic profile in 3 phase 1 studies [ 5 , 6 ]. VV116 targets the conserved viral RdRp, and demonstrated potent antiviral activities against the omicron variant with an EC 90 of 0.30 μM, comparable to that of the original strain (EC 90 : 0.83 μM).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that VV116 showed potent activity against a panel of SARS-CoV-2 variants, including the Omicron variant [87] , [90] . In addition, VV116 exhibited satisfactory safety and tolerability in healthy subjects in phase I studies [89] . VV116 has been approved for the treatment of COVID-19 in Uzbekistan and is currently being investigated in phase II/III clinical trials in patients with COVID-19.…”
Section: Inhibitors Of Rdrpmentioning
confidence: 97%
“…As a deuterated, tri-isobutyrate ester prodrug of the RDV parent nucleoside, VV116 is rapidly metabolized into the parent nucleoside (116-N1) in vivo. 116-N1 is intracellularly converted to the nucleoside triphosphate active form, which would interfere with the function of RdRp, thus inhibiting SARS-CoV-2 replication [89] . It has been demonstrated that VV116 showed potent activity against a panel of SARS-CoV-2 variants, including the Omicron variant [87] , [90] .…”
Section: Inhibitors Of Rdrpmentioning
confidence: 99%
“…Notably, a deuterated, oral GS-441524 tri-isobutyrate ester prodrug (VV116) has entered phase III clinical trials for evaluating its efficacy against SARS-CoV-2 infection. [ [12] , [13] ] In this study, we synthesized different deuterated GS-441524 analogs at different position on the ribose and nucleobase moieties, and evaluated their efficacy against SARS-CoV-2 in vitro.…”
Section: Introductionmentioning
confidence: 99%